A Positive Babinski Reflex Predicts Delayed Neuropsychiatric Sequelae in Chinese Patients with Carbon Monoxide Poisoning. (14th May 2014) - Zou, Jian-Fang; Guo, Qiming; Shao, Hua; Li, Bin; Du, Yuxiu; Liu, Maofeng; Liu, Fengling; Dai, Lixin; Chung, Min-Hsien; Lin, Hung-Jung; Guo, How-Ran; Yang, Tzu-Meng; et al.
Abstract : As the human population increased in China, the carbon monoxide is a serious environmental toxin in public health. However, predicting the delayed neuropsychiatric sequelae (DNS) of carbon monoxide poisoning (COP) has not been well studied. We investigated the independent predictors of DNS in patients with COP. This study was conducted at four hospitals in China. Data were retrospectively collected from 258 patients with COP between November 1990 and October 2011. DNS was the primary endpoint. A positive Babinski reflex was the independent predictor for DNS: sensitivity = 53.8% (95% confidence interval [CI]: 26.1–79.6), specificity = 88.6% (95% CI: 83.7–92.1), positive predictive value (PPV) = 20.0% (95% CI: 9.1–37.5), and negative predictive value (NPV) = 97.3% (95% CI: 94.0–98.9). The area under the receiver operating characteristic curve = 0.712 (95% CI: 0.544–0.880). A positive Babinski reflex was very memorable, immediately available, and applicable in clinical practice. Even when the sensitivity and PPV of a positive Babinski reflex were unsatisfactory, it had a good specificity and NPV for excluding the risk of DNS. In patients without a positive Babinski reflex, the risk for DNS was only 2.7%. This finding may help physicians make decisions about dispositions for patients with COP.